Serum tumour marker (CEA, CA 19-9 and CA 27-29) levels and their association with clinicopathological parameters in Nigerian breast cancer patients - Ganiyu Olatunbosun Arinola; Mutiu Alani Jimoh; Kehinde Adigun; Mosunmade Babatunde Oshingbesan (Medical Research Journal)
INTRODUCTION: To hasten management and improve patients’ quality of life, there is a need for quick, cheap and accessible biomarkers of breast cancer prognosis following confirmatory diagnosis. Tumour markers are substances produced by the tumours or by other cells of the body in response to cancer or certain benign conditions, but the role of serum tumour markers in breast cancer prognosis remains controversial due to multiorgan sources of a biomarker. This study aimed to evaluate the association of serum carcinoembryonic antigen (CEA) and carbohydrate antigen (CA 19-9 and 27-29) levels with clinicopathological parameters in patients with breast cancer. MATERIALS AND METHODS: Sera from a total of 183 breast cancer patients of different clinic-pathological characteristics were analysed for CEA, CA 19-1 and CA 27-29 using a Hitachi automatic immunoassay analyser based on chemiluminescence principle. The mean values were compared using the Student t-test while the frequencies of prevalence were compared using the X2 test. RESULTS: Mean serum CA 19-9 level was significantly higher in well-differentiated compared with moderately- differentiated or ductal- compared with lobular- breast cancer patients. The mean serum CEA 19-9 level was significantly higher in ductal- compared with lobular- breast cancer patients. A higher prevalence of metastatic or moderately-differentiated breast cancer patients had levels of CA19-9 above reference ranges while a higher prevalence of stage 2 breast cancer patients had levels of CA 27-29 above reference ranges. CONCLUSIONS: CA 19-9 differentiates breast cancer histological grades and metastasis. Therefore, CA 19-9 provides additional insight into breast cancer clinicopathological types than CEA or CA 27-29.